Oncology Navigation Decreases Time to Treatment in Patients with Pancreatic Malignancy - Enomoto, Laura M.; Fenstermaker, Joyce; Desnoyers, Rodwige J.; Pasche, Boris C.; Blackstock, A. William; Howerton, Russell M.; Clark, Clancy J.; Levine, Edward A.; Shen, Perry (Annals of surgical oncology, 2019)
Background Care of pancreatic cancer patients has become increasingly complex, which has led to delays in the initiation of therapy. Nurse navigators have been added to care teams, in part, to ameliorate this delay. This study investigated the difference in time from first oncology visit to first treatment date in patients with any pancreatic malignancy before and after the addition of an Oncology Navigator. Methods A single-institution database of patients with any pancreatic neoplasm evaluated by a provider in radiation, medical, or surgical oncology between 1 October 2015 and 30 September 2017 was analyzed. After 1 October 2016, an Oncology Navigator met patients at their initial visit and coordinated care throughout treatment. The cohort was divided into two groups: patients evaluated prior to the implementation of an Oncology Navigator and patients evaluated after implementation. Patient demographics and time from first visit to first intervention were compared. Results Overall, 147 patients with a new diagnosis of pancreatic neoplasm were evaluated; 57 patients were seen prior to the start of the Oncology Navigator program and 79 were evaluated after the navigation program was implemented. On univariate analysis, time from first contact by any provider to intervention was 46 days prior to oncology navigation and 26 days after implementation of oncology navigation ( p = 0.005). While controlling for other covariates, employment of the Oncology Navigator decreased the time from first contact by any provider to intervention by almost 16 days ( p = 0.009). Conclusions Implementing an oncology navigation program significantly decreased time to treatment in patients with pancreatic malignancy.